Study of Flood Variation of Wainganga River Basin and Dhuti Dam with Impact on Crops at Balaghat Station (India) - Patle, S. K.; Parasar, C.; Chavan, R. (Universitas Pendidikan Indonesia (UPI), 2023)
The usefulness of the Dhuti dam and its importance for crop irrigation at the Balaghat station, located on the Waingang River in Madhya Pradesh, India, has been the focus of research on rainfall fluctuations in the Wainganga sub-basin. Wainganga is the largest peninsular river in India. Wainganga River flows for 635.40 kilometers. Until its confluence with the Wardha River, the Wainganga River has a catchment area of 51,000 km2. The basin spans the five districts of Maharashtra and three districts of Madhya Pradesh. The Wainganga Basin is also mentioned in